2016
DOI: 10.1016/j.apenergy.2015.10.119
|View full text |Cite
|
Sign up to set email alerts
|

Interval optimization based operating strategy for gas-electricity integrated energy systems considering demand response and wind uncertainty

Abstract: In the United States, natural gas-fired generators gained increasing popularity in recent years due to the low fuel cost and emission, as well as the proven large gas reserves. Consequently, the highly interdependency between the gas and electricity networks is needed to be considered in the system operation. To improve the overall system operation and optimize the energy flow, an interval optimization based coordinated operating strategy for the gaselectricity integrated energy system (IES) is proposed in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
164
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 359 publications
(165 citation statements)
references
References 26 publications
0
164
0
1
Order By: Relevance
“…The dispatch problem of an IES studied in this paper conducts in 1-hour interval [10][11][12]25]. In order to compromise the competing benefits of the electricity network, gas network, and distributed DHCs, the power trade-offs among them are investigated in detail by means of optimizing the selected objectives simultaneously.…”
Section: Integrated Energy System Modeling 21 System Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dispatch problem of an IES studied in this paper conducts in 1-hour interval [10][11][12]25]. In order to compromise the competing benefits of the electricity network, gas network, and distributed DHCs, the power trade-offs among them are investigated in detail by means of optimizing the selected objectives simultaneously.…”
Section: Integrated Energy System Modeling 21 System Descriptionmentioning
confidence: 99%
“…The gas flow from node m to node n through the compressor j, f mn , is mathematically expressed as [11]:…”
Section: Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…A stochastic-programming-based coordinative scheduling tool is presented in [16], in which wind power is described by scenarios. The model can also be formulated as interval [17] or robust optimization problems [18] by modeling the uncertainty using intervals or sets. Moreover, reference [19] shows that a strategic bidding strategy of GFUs can also be beneficial within the current market framework.…”
Section: Introduction Ccording To the Energy Information Administrmentioning
confidence: 99%
“…They concluded that the former requires a longer solution time but yields more robust results. Bai et al [39] applied interval optimization for optimization of gas-electricity integrated energy systems networks. They considered demand response and wind Please cite this publication at: Mahdi Sharifzadeh, Helena Lubiano-Walochik, Nilay Shah.…”
mentioning
confidence: 99%